COMPARATIVE STUDY OF REMOVAL POLLUTANTS ( HEAVY METALS) BY AGRICULTURAL WASTES AND OTHER CHEMICAL FROM THE AQUEOUS SOLUTIONS - J., Nisreen A.; Sirhan, M. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study included the application of some experiments in the chemical treatment of some heavy metals elements by preparing biological surfaces that are adsorbed from natural and other chemical substances, as in preparing activated carbon prepared from charred pistachio shell with concentrated H2SO4 and Nano-Calcium Oxide prepared from CaCL2.2H2O with NaOH . The prepared materials were diagnosed with spectral techniques where the FTIR infrared spectrum proved the formation of carbonyl, hydrogen and oxygenated of the surface in activated charcoal and the hydroxyl and calcium oxide groups in the nano-calcium oxide, as the FE-SEM surface morphology was proven to form on coal blocks The surface is a network of irregular holes and a network of microscopic holes regular on the surface of nano- calcium oxide. As for X-ray diffraction technology, the crystal structures of the surface, its shapes and sizes, are shown, and that activated charcoal consists of that Many types of carbon in the form hexagonally and cuboid and rhomboid with a right angle, while technical proven size of the crystalline calcium oxide nanoscale which ranges between (54.68-67.86nm) cube-shaped. PIAC activated charcoal and n-Calcium oxide were used as sorbents in the removal of, Cd + 2, Pb + 2 ions from aqueous solutions, a study of the effect of pH, contact time, multiple weights for surface and the primary concentration of ions in a horizontal removal method , and the removal of minimal concentrations of ions in large volumes of solutions by the process of preconcentration .